The relationship between personality traits and optimism in pets owners - Enache, Rodica; Sandu, Mihaela Luminița; Tocitu , Simona; Jeancă, Ana-Maria; Toma, Iuliana (Technium Social Sciences Journal, 2022)
Interaction with pets influences the social interaction between people and helps to develop self-confidence and confidence in others, empathy and a positive mood. This study aims to identify correlations between personality traits and optimism in people who have pets. The objective pursued is the following: establishing the state of affairs regarding the existence of correlations between personality traits and the level of optimism of people who have pets.